Strategi Komunikasi Pemasaran Anggrek Souvenir dalam Mempromosikan Produk - Anggreini, Mutia Erda; Hasmawati, Fifi; Trisiah, Anita (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "Orchid Souvenir Marketing Communication Strategy in Promoting Products". The aim of this research is to find out what marketing communication strategies Anggrek Souvenir uses in promoting products. This research uses descriptive qualitative methods, collecting data through observation, interviews and documentation. This research uses the concept of marketing mix theory and promotion mix. The results of this research, Orchid Souvenir, apply the concept of marketing mix theory which consists of product, price, place and promotion. and the concept of promotional mix theory, namely advertising, sales promotion, personal/face-to-face selling, public relations and direct marketing to promote products to buyers. Of all the promotional mixes implemented by Anggrek Souvenir, the advertising strategy carried out by posting product photos on social media is not very active and utilized, even though nowadays other business people use social media to promote their products. However, sales promotion is the most effective strategy used by Anggrek Souvenir in promoting its products.